Natural Convection Heat Transfer of a Viscous Fluid in a Vertical Porous Channel - Siginer, D (2012)
Approximate analytic solutions to second-order nonlinear systems arising in natural convection flow and heat transfer in vertical porous channels are obtained via the Galerkin-Legendre Spectral Method. Furthermore, existence, uniqueness, and concavity results are established using Green s functions and degree theory. We find that an increase in either the Darcy number or the quadratic density temperature variation results in an increase in the velocity and the temperature of a Newtonian fluid. Finally, parametric zones for the occurrence of reverse flow are considered, and the resulting influences on the obtained approximate solutions are analyzed. © 2011 Springer Science+Business Media B.V.